Developing Quality in The Phases of The Product Life Cycle – Case Study - Zbigniew SKUZA; Rafal PRUSAK (Communications of International Proceedings, 2024)
The aim of the article is to present the process of influencing the quality of a product in individual phases of its life cycle. Particular attention was paid to customer relations as well as the method of obtaining information and supplementing the knowledge base. It has been shown that these factors, together with human capital, have a decisive impact on the market position of the analyzed case. The work of the team that supervised a specific product design from the idea of its creation to the care of the product after sale was discussed.
Keywords: quality management; product life cycle; knowledge management